Managing ulcerative colitis after surgery - Calvino-Suarez, Cristina; Ferreiro-Iglesias, Rocío; Baston Rey, Iria; Barreiro-de Acosta, Manuel (Frontiers in Medicine, 2023)
Management of ulcerative colitis after surgery suggested by guidelines (total proctocolectomy with ileal-pouch anal anastomosis) is a big challenge for physicians because patients who believed that their disease had been cured started experiencing very uncomfortable symptoms repeatedly. A high number of patients develop episodes of pouchitis, which is a non-specific inflammation of the pouch whose etiology is unknown. Antibiotics are the elective treatment for acute pouchitis, but regarding chronic pouchitis, this condition is very complicated to treat due to the absence of well-designed specific studies for this group of patients. Antibiotics, budesonide, and biological therapies are some of the recommended drugs for these patients, but despite their use, some need a permanent ileostomy.